Improvement of Biodegradability of Synthetic Amoxicillin Wastewater by Photo-Fenton Process - Elmolla, E. S.; Chaudhuri, M. (IDOSI, 2009)
Antibiotics are emerging contaminants in the aquatic environment because of their adverse effects on aquatic life and humans. Antibiotic wastewater has high COD and very low BOD5, and hence is difficult to treat biologically. The objective of this research was to study the effect of operating conditions (reaction time, pH, H2O2 dose and Fe2+ dose) of the photo-Fenton process in improving the biodegradability of a synthetic amoxicillin wastewater. In addition, degradation of amoxicillin by the photo-Fenton process under optimum operating conditions was studied. These conditions had a great effect on biodegradability (BOD5/COD ratio) improvement. Maximum biodegradability (0.55)was at reaction time 45 min, H2O2/COD molar ratio 2:1, H2O/Fe2+ molar ratio 50:1 and pH 3. Under optimum operating conditions, complete degradation of amoxicillin was achieved in one min. The photo-Fenton process is considered a suitable pretreatment method to improve the biodegradability of antibiotic wastewater.